The Effectiveness of Information Technology Implementation on Improving the Quality of Learning of Elementary School Students in the New Normal Era - Izza, Intana Aura; Dewi, Nesa Artika; Af’idatussofa, Hilda; Ningrum, Amanda Ayu; A’la, M. Haikal Emirza (Jurnal Inovasi Pembelajaran Karakter, 2025)
The application of information technology in learning is the primary strategy in answering education challenges in the new normal era, especially at the primary school level. The transformation of learning from face-to-face to online and hybrid learning models demands innovative and effective digital media. This research aims to examine the effectiveness of the application of information technology to improve the quality of learning of elementary school students, with an emphasis on interactive learning media, online platforms, and digital educational content development. The method used is descriptive qualitative, based on literature review and case analysis in elementary schools. The results show that information technology can increase motivation, material understanding, and active student involvement in the learning process. Platforms such as Google Classroom, Zoom, and animated video media are proven effective in creating an enjoyable learning atmosphere and are adaptive to students' learning styles. However, challenges such as limited internet access, device gaps, and teacher competence in using technology still need to be overcome collaboratively. Therefore, the implementation of information technology is considered adequate and needs to be continuously improved to support the quality of basic education that is equitable and competitive.